Institutions and ideology - Meyer, Renate E. (Emerald, 2006)
This volume contributes to the literature on the sociology of organizations and management, especially to sociological institutionalism, by attempting to fill an important gap in institutional research. Our starting point is the conviction that organizational institutionalims is the conceptual and empirical venue to study ideology, both in its symbolic and material dimension and this volume represents an effort to refocus and revitalize these issues. The ten chapters of this volume engage directly and critical with several North American and European institutional traditions. Apart from organizational institutionalism's own classic and current research, they draw on a wide variety of theoretical legacies to make sense of the relationship between institutions and ideology: Weber, Foucault, Heidegger, Bourdieu, Archer, Wuthnow, critical discourse analysis, or Kuhn's discussion of paradigm shifts as ideological changes. Empirical areas covered range from technology and software development, the brewing industry, custodial facilities to the organization of birthing.